2020
DOI: 10.1016/j.cegh.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its components among a population-based study in south of Iran, PERSIAN Kharameh cohort study

Abstract: Objectives: over the past few years, lifestyle modification has increased the prevalence of major components of metabolic syndrome (MetS), leading to increased risk of non-communicable diseases, especially cardiovascular disease. The present study was aimed to determine the prevalence of MetS and its components and present results according to the major demographic characteristics of the participants in a population-based study. Methods: This cross-sectional study was conducted on a total of 10663 subjects age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
(54 reference statements)
4
10
2
Order By: Relevance
“…This study found that the overall prevalence of MetS was 20.6%. The prevalence rate reported in this study was higher than that found in Taiwanese high-tech industry workers (8.2%) 42 , the Philippine general population (18.6%) 43 and a rural Ugandan adult cohort (19.1%) 44 , but lower than that found in populations across Iran (ranged between 33.1% and 37.1%) 26 , 45 , Brazil (34.1%) 24 , Indonesia and the Netherlands (39% vs. 29.2%) 46 , China (ranged between 24.2 and 42.6%) 23 , 25 , 31 , Canada (25%) 47 and Australia (ranged between 21.1 and 30.7%) 48 . From the Malaysian context, population-based prevalence estimates for MetS ranged between 25 and 40% 9 , 16 , 49 , while for specific sub-groups, the prevalence rates of MetS for patients with type 2 diabetes mellitus ranged between 73 and 85% 50 , among elderly people was 43.4% 51 , non-diabetic women post gestational diabetes mellitus was 22% 52 , and for vegetarians accounted for approximately 24.2% 53 .…”
Section: Discussioncontrasting
confidence: 79%
“…This study found that the overall prevalence of MetS was 20.6%. The prevalence rate reported in this study was higher than that found in Taiwanese high-tech industry workers (8.2%) 42 , the Philippine general population (18.6%) 43 and a rural Ugandan adult cohort (19.1%) 44 , but lower than that found in populations across Iran (ranged between 33.1% and 37.1%) 26 , 45 , Brazil (34.1%) 24 , Indonesia and the Netherlands (39% vs. 29.2%) 46 , China (ranged between 24.2 and 42.6%) 23 , 25 , 31 , Canada (25%) 47 and Australia (ranged between 21.1 and 30.7%) 48 . From the Malaysian context, population-based prevalence estimates for MetS ranged between 25 and 40% 9 , 16 , 49 , while for specific sub-groups, the prevalence rates of MetS for patients with type 2 diabetes mellitus ranged between 73 and 85% 50 , among elderly people was 43.4% 51 , non-diabetic women post gestational diabetes mellitus was 22% 52 , and for vegetarians accounted for approximately 24.2% 53 .…”
Section: Discussioncontrasting
confidence: 79%
“…In primary analysis of GCS, diabetes was more prevalent in females (27.3%) rather than males (20.2%) (17). The nding of PERSIAN Kharameh cohort study showed that subjects living in urban areas were more likely to display metabolic syndrome and DM than those living in rural areas [23]. Contrary to our study in Kharameh cohort study, prevalence of impaired fasting glucose in females was higher than males.…”
Section: Roc Curve Analysiscontrasting
confidence: 94%
“…Distribution of ADA risk score Figure 2 presents the frequency of ADA risk scores among participants. The mean ADA risk score for all respondents were 4.48 (SD = 1.55), and using a recommended cut-off values, the prevalence of high risk subjects for preDM and DM were, 23.9% (n = 1912) and 48.5% (n = 3874), respectively.…”
Section: Characteristics Of the Participantsmentioning
confidence: 98%
“…For body mass index participants were divided into the following groups: low weight (BMI < 18.5 kg/m2), normal weight (BMI = 18.5-24.9 kg/ m2), overweight (BMI =25-29.9 kg/m2), and obesity (BMI ≥ kg/m2). Also, the following blood biochemical parameters were used as components of MetS: fasting plasma glucose (FPG), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) [28,29].…”
Section: Methodsmentioning
confidence: 99%